Between Miltiades and Moltke: Early German Studies in Greek Military History - Konijnendijk, Roel (Brill Research Perspectives in Humanities and Social Sciences., 2023)
The authors of the first serious scholarly works on Greek warfare were not free to write their surveys as they wished. In the nineteenth-century German-speaking world, the supreme authority on all military history rested with the Great General Staff, the intellectual nerve centre of the Prussian army. Officers rejected the ability of historians to understand warfare and imposed their pragmatic perspective on any attempt to study past wars. How did classicists and historians respond to this challenge? This book explores how the scope and method of the first handbooks on Greek warfare were shaped by their environment; it questions the ancient wisdom that practical expertise is the best guide to writing military history.